2014
DOI: 10.1111/ped.12208
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric surgeon vs general surgeon: Does subspecialty training affect the outcome of appendicitis?

Abstract: Overall complication rates were similar between PS and GS. Complications were significantly more prevalent in patients with complicated appendicitis who were treated by GS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 18 publications
(100 reference statements)
0
28
0
Order By: Relevance
“…Two studies (63,282 children) were retrospective analyses of registry-based hospital discharge data. 13 , 18 The other 7 studies (2713 children) concerned specified institutions and were either single-center 12 , 17 or multicenter. 8 , 11 , 14 16 Recruitment dates for included studies spanned the period from 1993 to 2012.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies (63,282 children) were retrospective analyses of registry-based hospital discharge data. 13 , 18 The other 7 studies (2713 children) concerned specified institutions and were either single-center 12 , 17 or multicenter. 8 , 11 , 14 16 Recruitment dates for included studies spanned the period from 1993 to 2012.…”
Section: Resultsmentioning
confidence: 99%
“…No study reported explicitly on criteria that determined whether patients were managed by general surgery teams or pediatric surgery teams – however we think that allocation is likely to have reflected the nature of the on-call team and available resources at any particular time. Most of the studies reported on the proportions of patients who underwent laparoscopic or open appendicectomy procedures 8 , 11 , 12 , 14 , 16 , 17 although these data were not reported in some studies. 13 , 15 , 18 , 19 Few studies reported conversion rates from laparoscopic to open surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that specialized surgeons produce better outcomes than general surgeons after general thoracic surgical procedures [ 25 ]. In another study, adverse events after complicated appendicitis were significantly more prevalent for those who were treated by general surgeons than by pediatric surgeons [ 26 ]. In our study, however, no differences in short-term adverse events or readmission were found between pediatric and nonpediatric orthopedic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Acute appendicitis is the most common disease requiring emergency surgery, with surgeons performing 81,000 appendectomies annually in the United States 9 . Similarly, in Australia, surgeons perform 27,000 appendectomies every year 4,5,10,11 .…”
Section: Introductionmentioning
confidence: 99%